COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH IN LANGUAGE TEACHING (Web of Teachers: Inderscience Research, 2025)
The Communicative Language Teaching (CLT) approach has emerged as one of the most influential methodologies in teaching English as a Foreign Language (EFL). This article explores the principles, advantages, and challenges of implementing CLT in EFL classrooms. It also highlights the theoretical underpinnings and practical applications of the approach. Drawing on relevant studies, this article provides insights into how CLT can enhance learners' communicative competence and addresses the barriers faced by teachers and learners in diverse educational contexts.